Baker’s Method in the Management of Equinus Deformity in Cerebral Palsy - Datta, NK; Kaiser, MS; Saha, BK; Ahammed, SU; Choudury, AI (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):533-38 The abstract of this article is available on the PubMed website